Estimation of Theoretical Flame Temperatures for Claus Sulfur Recovery Unit Using a Simple Method - Bahadori, Alireza; Vuthaluru, Hari (TAYLOR & FRANCIS INC, 2013)
Recovery of elemental sulfur from industrial waste gases is an important problem both from environmental and economic perspectives. The most widely used process is the Claus process, where one-third of the acid gas is oxidized to SO2 in a reaction furnace using air. This combustion generates a large amount of heat. Further, the combustion products undergo Claus reaction between H2S and SO2. The aim of this study is to develop a simple-to-use predictive tool suitable for combustion engineers, which is easier than existing approaches less complicated with fewer computations for predicting the theoretical flame temperature for both straight-through operation and for a split-flow operation with two-thirds of the acid gas bypassing the combustion section. The proposed tools are formulated as a function of the temperature of the acid gas feeding the combustion section and the hydrogen sulphide mole fraction (dry basis) in feed gas. Results show that the proposed predictive tool has a very good agreement with the reported data where the average absolute deviation percent is less than 0.1%. The proposed method is superior owing to its accuracy and clear numerical background, wherein the relevant coefficients can be retuned quickly for various cases. This proposed simple-to-use approach can be of immense practical value for engineers and scientists to have a quick check on theoretical flame temperature for both straight-through operations as well as for a split-flow operation for a wide range of operating conditions without the necessity of any pilot plant set up and experimental trials. In particular, process and combustion engineers would find the proposed approach to be user friendly involving transparent calculations with no complex expressions for their applications to the design and operation of sulfur recovery Claus unit.